Analisis Faktor-Faktor yang Berhubungan dengan Keinginan Pindah Kerja Perawat Rumah Sakit X Balikpapan Tahun 2014 - Indrayani, Susila (UI Scholars Hub, 2016)
This is a descriptive analytical study with quantitative and qualitative design aim to descripe and analysis factors related to move out of nurses at the X hospital Balikpapan. The study collected using questionnaire to 199 nurses, followed by in-depth interviews to 5 senior management, 1 chief ward and 1 secretary of nursing committe of hospital. Career development, compensation, and communication are the mean factors related to the intention to move out, communication is the most factor influencing the intention to move out. Qualitative methode validated the important communication between the management and the nurses which is not in a good condition. The management should formed a special meeting for nurses to collect the aspiration nurses in order to increase the sense of involvement which decrease the desire to move out.